Power Losses of Spiral Bevel Gears: An Analysis Based on Computational Fluid Dynamics - Mastrone, Marco Nicola; Concli, Franco (Frontiers in Mechanical Engineering, 2021)
Energy efficiency is among the predominant aspects in mechanical design. Geared transmissions are widespread in several industrial applications and efficiency’s improvements translate into various benefits, e.g. reduction of pollutants’ emissions, better system’s reliability due to lower operating temperatures, and higher power density. The optimization of the layout of gearboxes leads to the reduction of the mass of the system leaving more space for other components. The possibility to compare different solutions in the preliminary stages of the design phase plays a determinant role to the achievements of these targets. The analytical equations derived from experiments have many limitations, mainly related to the range of applicability in terms of geometrical configuration, physical properties and operating conditions. Thanks to recent advancements in computer science, engineers can investigate the problem exploiting simulation software packages. In particular, Computational Fluid Dynamics (CFD) can be adopted to analyze the problem of interest overcoming the limitations of the analytical equations. On the other side, the application of numerical models to gears, in which the topology of the domain changes during operation, represents a challenging task and tailored mesh handling algorithms must be implemented. In the current paper, the power losses of a spiral bevel gear were examined numerically with an opensource tool. The predictions of the numerical models were compared with experimental data. The approach adopted shows a good computational effort making it useful for parametrical studies and, therefore, suggests being an effective tool for the analysis of the gearboxes’ efficiency and lubrication.